Pengelolaan Perpustakaan dalam Meningkatkan Minat Baca Siswa SMA Negeri 1 Tibawa Kecamatan Tibawa Kabupaten Gorontalo - Diu, Sri Yulan S.; Nggilu, Rukiah (Innovative: Journal Of Social Science Research, 2024)
This study aims to determine and analyze "Library Management in Increasing Reading Interest of Students of SMA Negeri 1 Tibawa, Tibawa District, Gorontalo Regency". The research method used in this study is a qualitative descriptive method. The results of the Management study, there are several problems including the number of books is still lacking, there are still many books that are not available, human resources on duty in the library are still lacking so that services are not running optimally and library facilities and infrastructure are still lacking and inadequate It is recommended that the school needs to add and complete reference books, it is necessary to add library staff, especially librarians who are truly proficient in managing libraries, it is necessary to add supporting facilities and infrastructure for the library in order to increase students' reading interest Keywords: Management, Library, SMA Negeri 1 Tibawa